Evaluation and Restoration of Corrosion-Damaged Post-Tensioned Concrete Structures - Alsuwaidi, Hadif; Al-Sadoon, Zaid A.; Altoubat, Salah; Barakat, Samer; Junaid, M. Talha; Maalej, Mohamed; Metawa, Abdulrahman; Habib, Ahed (Salehan Institute of Higher Education, 2024)
This study addresses the pressing issue of chloride-induced corrosion in post-tensioned (PT) concrete structures, known for their strength and flexibility yet vulnerable to durability issues in extreme climates. The objective is to evaluate corrosion mechanisms in a PT building in the United Arab Emirates and develop a robust restoration strategy. Using a combination of nondestructive and semi-destructive testing methods, this research identifies severe deterioration in critical structural elements, such as steel tendons, PT ducts, and concrete surfaces, largely due to high chloride exposure and aggravated by environmental factors like acid rain and fluctuating temperatures and humidity. The findings reveal serious inadequacies in current maintenance practices, often overlooking long-term corrosion risks in harsh climates. In response, this study proposes a comprehensive repair strategy, including removing damaged materials and applying advanced repair products, protective coatings, and waterproofing measures to enhance the structure's durability. This case study highlights significant concerns regarding structural integrity and provides practical insights into effective maintenance and repair strategies for PT structures. By offering a targeted, sustainable intervention approach, this research contributes to developing PT maintenance protocols, particularly in regions prone to aggressive corrosion, ensuring the longevity and safety of these critical structures. Doi: 10.28991/CEJ-2024-010-12-02 Full Text: PDF